Fatores críticos que afetam a qualidade e segurança dos ovos de galinhas poedeiras: revisão de literatura - Pereira, Letícia Albuquerque Fortes [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
In the global scenario, Brazil ranks as the seventh largest egg producer, with the majority of its production being directed towards the domestic market. The high productivity coupled with a good consumption of this highly nutritious food is directly related to the assessment of the external and internal quality of the product, both by the producer and the consumer, who have different considerations regarding the egg’s attributes. However, there is consensus that a combination of factors, such as bird genetics, age, management practices, rearing systems, nutrition, handlers, stress as well as temperature, storage and management of the final product, influence the expression of the genetic potential acquired by layng hens over the years, thereby altering the egg’s quality and safety. Thus, the production of quality eggs, characterized by clean and intact shell, as well as a favorable proportion of internal componentes and an extended shelf life, is directly associated with previous processes and storage performed correctly. Proper control of these aspects is essential to ensure the marketing of a safe product

No cenário global, o Brasil é o sétimo país em produção de ovos, sendo majoritariamente destinado ao mercado interno. A elevada produtividade associada à um bom consumo desse alimento altamente nutritivo possui relação direta com a avaliação da qualidade externa e interna do produto, tanto pelo produtor quanto pelo consumidor, que possuem considerações distintas sobre as propriedades do ovo. Porém é de concordância que um conjunto de fatores, como a genética das aves, idade, manejo, sistema de criação, nutrição, manipuladores, estresse, bem como temperatura, armazenamento e manejo do produto final, interferem na expressão do potencial genético adquirido pelas galinhas poedeiras ao longo dos anos e assim, modificam a qualidade e segurança do ovo. Dessa forma, a produção de ovos de qualidade, com casca limpa e íntegra, bem como uma boa proporção de seus componentes internos, com um maior tempo de vida útil na prateleira, está diretamente associada aos processos anteriores e de armazenagem realizados de forma correta. O controle adequado desses aspectos é essencial para garantir uma comercialização de um produto seguro
Critical factors affecting the quality and safety of eggs from laying hens: a literature review
Keywords: Galinhas poedeiras; Laying hens; Manejo; Qualidade de ovos; Sanidade; Management; Egg quality; Health